Transparansi dan Efisiensi dalam Pendaftaran Tanah Melalui Era Undang-Undang Cipta Kerja - Veronika Lasma Silitonga; Atik Winanti (Jurnal Interpretasi Hukum, 2024)
Technological developments mean that the government must also participate in advancing forms of community services, one of which is in the land registration services sector. Land registration is the most important process in land activities, which is a form of creating legal certainty for the community. Because one of the most cases in Indonesia concerns land, a system is needed that can at least reduce land cases and create legal certainty for the community. Electronic land registration was realized through the Job Creation Law on October 5 2020, Indonesia is one of the countries that has just used an electronic land registration system. Singapore was one of the countries that first used an electronic registration system. Singapore realized that there was a need for an integrated land and building system for planning. The electronic system creates various conveniences, with the applications and websites provided by BPN making it easy for people to carry out land activities anywhere and at any time. With this convenience, it will create efficiency and transparency for the community, so that legal certainty will also be fulfilled.